Android-Based Car Rental System with Customer Risk Management for MSMEs - Ridwansyah (Universitas Mohammad Husni Thamrin, 2026)
The development of information technology has become a major factor in driving digital transformation in various business sectors, including Micro, Small, and Medium Enterprises (MSMEs). Digital transformation through the use of information systems has been proven to improve organizational performance, support innovation, and improve data-based decision-making processes at the small and medium business scale. Manual recording is still frequently used by Micro, Small, and Medium Enterprises (MSMEs), including those engaged in the car rental sector. This practice can create vulnerabilities to recording errors, resulting in inaccurate information. To address this problem, this study developed an Android-based car rental system to assist business owners in managing their operational activities. The research stages referred to the System Development Life Cycle (SDLC) method, using the Waterfall model. The resulting system includes customer data management, rental transactions, and rental duration. In addition, the system is equipped with a blacklist feature. This feature is a customer risk management feature that blocks problematic customers based on their previous transaction history. To ensure the suitability of the system's functions, Black Box Testing was conducted. The test results showed that all the system features functioned as expected. The results of this study are expected to help car rental business owners monitor daily operational activities, including avoiding the risk of car loss due to problematic customers.